Development of the emerging electromagnetic methods for deep earth exploration. (31st May 2019) - Di, Qingyun; Xue, Guoqiang; Wang, Zhongxing; An, Zhiguo; Fu, Changmin; Wang, Ruo; Lei, Da; Olalekan, Fayemi
Abstract: Three emerging techniques for surface electromagnetic (EM) exploration with high detection accuracy and large depth of investigation, namely, WEM (wireless electromagnetic method), MTEM (multi‐channel transient electromagnetic method) and SOTEM (short‐offset grounded‐wire TEM), are introduced. In detail, we proposed a newly developed sky‐wave theory in which EM wave can propagate in full space of ionosphere‐atmosphere‐lithosphere. Correspondingly, we developed the WEM recording system to measure the sky‐wave to obtain the structures down to ∼10 km depth. We then introduced MTEM as a highly effective method for mineral exploration with target depth of 3km. Using self‐developed MTEM system, we presented the results obtained from mineral exploration study carried out in China. Lastly, we proposed the SOTEM method for a greater detection depth (1.5km) than traditional loop source TEM (500m) with a small offset and high resolution.